Cultural Development in Analysis of the Evolutionary Paradigm, Diffusion and Structural Functional - Ulung Napitu; Corry; Wilson Simanjuntak; Bakhrul Khair Amal (SIASAT, 2022)
This research aims to examine the process of cultural development analyzed from the perspective of the evolutionary, diffusion, and structural-functional paradigm. The importance of this analysis in the study of various anthropological paradigms is that no matter how simple society, it is absolutely necessary to experience gradual and revolutionary changes in development and culture. These changes lead to the disruption of socio-cultural values in people's lives. The approach used in this study is a qualitative approach with the biographical method. In collecting, processing and analyzing data, the authors searched for various literatures which were followed up with content analysis by comparing, and selecting various contents of literature books to formulate conclusions. The results of the study show that in the life of a very simple and complex society, socio-cultural changes are found. The results of the analysis based on the paradigm of evolution, diffusion and functional structure in the midst of an increasingly complex society found the disruption of socio-cultural values due to the dynamics of society, the rapid development of science and technology.